2011
DOI: 10.1007/s00380-011-0163-z
|View full text |Cite
|
Sign up to set email alerts
|

Plasma endoglin as a marker to predict cardiovascular events in patients with chronic coronary artery diseases

Abstract: Recent clinical studies have revealed that the expression of endoglin, an accessory protein for the TGF-β receptor, is increased in patients with atherosclerotic diseases. The plasma endoglin level is thought to represent endothelial activation, inflammation, and senescence. To clarify the significance of plasma endoglin in chronic coronary artery disease. Human umbilical vein endothelial cells (HUVECs) were cultured to examine changes in soluble endoglin (s-endoglin) levels caused by atherogenic stimulation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 31 publications
2
37
0
5
Order By: Relevance
“…Our results are consistent with a previous report showing that plasma sEng concentration could serve as an indicator of diabetes-associated vascular pathologies such as retinopathy, hypertension, endothelial dysfunction, and cardiovascular risk [45]. Similarly, another study demonstrated that sEng could be a marker to predict cardiovascular events in patients with chronic coronary artery disease [46]. In addition, Li et al [28] showed that plasma sEng is a valuable surrogate angiogenic marker for identifying breast cancer patients who are at high risk of developing metastasis.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are consistent with a previous report showing that plasma sEng concentration could serve as an indicator of diabetes-associated vascular pathologies such as retinopathy, hypertension, endothelial dysfunction, and cardiovascular risk [45]. Similarly, another study demonstrated that sEng could be a marker to predict cardiovascular events in patients with chronic coronary artery disease [46]. In addition, Li et al [28] showed that plasma sEng is a valuable surrogate angiogenic marker for identifying breast cancer patients who are at high risk of developing metastasis.…”
Section: Discussionsupporting
confidence: 93%
“…The magnitude of the differences in sEng concentrations between hypertensive OSA and control groups in our study is comparable to those seen with target organ damage and hypertension and in those with high risk for cardiovascular adverse outcome. 29,30 The mechanism for elevated sEng levels in OSA is unknown. However, there are several possibilities.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, spontaneous AVMs, the most frequent cause of cerebral haemorrhage in the young, may relate to abnormal function of ENG or ACVRL1 genes. In the context of general cardiovascular health, circulating Sol-Eng is not only an important biomarker of pre-eclampsia, but also a predictor of cardiovascular events in chronic coronary artery disease patients [68]. It is almost certain that further fundamental roles of endoglin and ACVRL1 in the cardiovasculature will be revealed in the near future.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%